Examining the ethical complexities of medical assistance in dying for individuals with serious mental illness - Kotze, Carla (Stellenbosch : Stellenbosch University, 2025)
Kotze, Carla. 2025. Examining the ethical complexities of medical assistance in dying for individuals with serious mental illness. Unpublished masters thesis. Stellenbosch: Stellenbosch Univeristy [online]. Available: https://scholar.sun.ac.za/handle/10019.1/132597